Cytocompatibility and cell proliferation evaluation of calcium phosphate-based root canal sealers - Letícia Boldrin Mestieri; Ivana Maria Zaccara; Lucas Siqueira Pinheiro; Fernando Branco Barletta; Patrícia Maria Polli Kopper; Fabiana Soares Grecca (Restorative Dentistry & Endodontics, 2020)
ObjectivesThis study aimed to evaluate the cell viability and migration of Endosequence Bioceramic Root Canal Sealer (BC Sealer) compared to MTA Fillapex and AH Plus.Materials and MethodsBC Sealer, MTA Fillapex, and AH Plus were placed in contact with culture medium to obtain sealers extracts in dilution 1:1, 1:2 and 1:4. 3T3 cells were plated and exposed to the extracts. Cell viability and migration were assessed by 3-(4,5-dimethyl-thiazoyl)-2,5-diphenyl-tetrazolium bromide (MTT) and Scratch assay, respectively. Data were analyzed by Kruskal-Wallis and Dunn's test (p < 0.05).ResultsThe MTT assay revealed greater cytotoxicity for AH Plus and MTA Fillapex at 1:1 dilution when compared to control (p < 0.05). At 1:2 and 1:4 dilutions, all sealers were similar to control (p > 0.05) and MTA Fillapex was more cytotoxic than BC Sealer (p < 0.05). Scratch assay demonstrated the continuous closure of the wound according to time. At 30 hours, the control group presented closure of the wound (p < 0.05). At 36 hours, only BC Sealer presented the closure when compared to AH Plus and MTA Fillapex (p < 0.05). At 42 hours, AH Plus and MTA Fillapex showed a wound healing (p > 0.05).ConclusionsAll tested sealers demonstrated cell viability highlighting BC Sealer, which showed increased cell migration capacity suggesting that this sealer may achieve better tissue repair when compared to other tested sealers.